Climate responsive architecture : a design handbook for energy efficient buildings - Krishan, Arvind; Baker Nick.; Yannas Simos; Szokolay S. V. (New Delhi ; New York : Tata McGraw-Hill Pub. Co., 2001)
Papers presented at an international workshop held in 1995.
Keywords: Dwellings -- Energy conservation -- Congresses